AN ANALYTICAL INVESTIGATION OF A VARIABLE-COMPLIANCE-TYPE CONSTITUTIVE EQUATION - Okubo S.; Fukui K. (My University, 2006)
A constitutive equation is proposed in which the compliance is assumed to monotonically increase as a load is applied. The primary feature of the constitutive equation is that the equation can be applied to various loading conditions such as constant stress rate, constant strain rate, creep, or relaxation. The second feature is that the equation has exact solutions under many loading conditions. The present paper shows the exact solutions for the constitutive equation and investigates the mutual relationships between the exact solutions for the different loading conditions. The third feature is that it is comparatively easy to find the constants in the constitutive equation. The present paper shows how to solve the constitutive equation for the constants, and the constants for some native Japanese rocks. The constitutive equation used in the present paper is extremely simple. Therefore, the equation can be easily implemented in almost any FEM code. It is likely that additional terms of the constitutive equation will prove necessary for practical usage. However, additional terms can be found very easily by finding higher-order approximations of experimental data.
Keywords: ROCK; CONSTITUTIVE EQUATION; ANALYSIS; VISCOELASTICITY; CREEP; RELAXATION